1991
DOI: 10.1159/000186304
|View full text |Cite
|
Sign up to set email alerts
|

Low-Protein, Low-Phosphorus Diet and Tissue Insulin Sensitivity in Insulin-Dependent Diabetic Patients with Chronic Renal Failure

Abstract: Tissue insulin sensitivity was measured by the glucose clamp technique in 8 uremic insulin-dependent diabetic patients before and after 3 months on a low-protein diet (LPD) providing daily 35 kcal/kg body weight, 60% of the caloric supply being obtained from carbohydrates. An improvement in tissue insulin sensitivity was observed for each steady state of the clamp and daily insulin requirements decreased significantly from 38.3 ± 3.2 to 28.2 ± 2.5 units (p < 0.01) in spite of an increased carbohydrate intake. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…Glycerol's contribution to gluconeogenesis is not included in these estimates. Studies with H, [3][4][5][6][7][8][9][10][11][12][13][14] C]-lactate have shown that equilibrium of the hydrogen bound to carbon 6 with that in body water was 80±90 % complete, so that gluconeogenesis is underestimated by 10±20 % [13]. This corresponds to our results and implies that the 13C-glucose method is valid under the conditions of the experimental design of our study.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Glycerol's contribution to gluconeogenesis is not included in these estimates. Studies with H, [3][4][5][6][7][8][9][10][11][12][13][14] C]-lactate have shown that equilibrium of the hydrogen bound to carbon 6 with that in body water was 80±90 % complete, so that gluconeogenesis is underestimated by 10±20 % [13]. This corresponds to our results and implies that the 13C-glucose method is valid under the conditions of the experimental design of our study.…”
supporting
confidence: 87%
“…Manipulation of protein ingestion has been used to slow down diabetic nephropathy [1]. Furthermore, epidemiological studies indicate that the quantity and quality of protein ingestion affects the expression of Type I (insulin-dependent) diabetes mellitus [2,3]. We have previously shown that a high protein diet accelerates the progression of the autoimmune loss of endogeneous insulin secretion in patients with Type I diabetes [4,5].…”
mentioning
confidence: 99%
“…Interestingly, meat protein has been implicated in diabetic renal disease due to its effect on the glomerular filtration rate [16] . Also, when people with diabetic nerve damage switch to a vegan diet (no meat, dairy or eggs), evidence has supported improvements in renal function [17,18] and glucose tolerance [19] .…”
Section: Introductionmentioning
confidence: 99%
“…74 Prospective studies and a recent meta-analysis demonstrate that reducing the dietary protein content reduces the accumulation of uremic toxins and phosphate and may improve symptoms and metabolic derangements. 67,75 In a Cochrane review, Fouque et al 76 observed that in CKD patient Stages 4-5 that follow an LPD, the progression to end-stage kidney disease was arrested.…”
Section: Low-protein Diet For Nondialysis Chronic Kidney Disease Patimentioning
confidence: 99%